Real-time implementation of a combined controller-observer approach for shunt active filters - Kiran, Nagulapati; Naidu, I. E. S. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The crucial role of shunt active power filter (SAPF) is to compensate for reactive power, balances unbalanced currents and counteract harmonics produced due to non-linear loads, by injecting phase-opposed compensation current by designing an appropriate controller. In this work, a combined controller-observer state and disturbances estimation scheme for a SAPF is proposed. To avoid the requirement of full-state feedback, unknown input observers (UIO) is designed. This is conducted in OPAL-RT OP4510 environment. Real-time simulations are used to show how successful the suggested controller-observer architecture for SAPF is; wherein the estimated states from the observer are fed back to the controller, and finally, the disturbance is also estimated. UIO is designed for SAPF to deal with nominal conditions and in the presence of sinusoidal disturbance.The OPAL-RT results clearly show that LO introduces steady state error between the reference input and the estimated state of SAPF in the presence of disturbances. This steady state error is completely eliminated in presence of all disturbances using UIO. The results also show that UIO perfectly tracks the reference input in the presence of disturbances. Further, disturbances are also estimated perfectly with UIO.